Low dielectric loss PTFE in-situ fiberized FEP microporous material, preparation method and application in wave-transmitting materials

By adding PTFE fibers to FEP materials and using supercritical foaming technology, the problems of poor dielectric performance and large wave transmission loss of FEP materials in wave-transmissive equipment are solved, and low dielectric constant and high foaming ratio are achieved. Suitable for high-frequency PCB board requirements.

CN116144127BActive Publication Date: 2024-12-24SICHUAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210898442.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-28
Publication Date
2024-12-24
Estimated Expiration
2042-07-28

AI Technical Summary

Technical Problem

The existing FEP materials have problems of low dielectric performance and large wave transmission loss in wave transmitting equipment, which limits their application in high-frequency signal transmission.

Method used

By adding PTFE fibers to the FEP material, a low dielectric loss PTFE in-situ fiber FEP microporous material is prepared by supercritical foaming method to improve rheological processing performance and reduce dielectric constant.

Benefits of technology

It significantly reduces the dielectric constant and dielectric loss, improves foaming magnification and wave transmission performance, and is suitable for high-frequency and high-speed PCB board applications, maintaining other excellent properties of the material such as flame retardant, hydrophobic and corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116144127B_ABST
    Figure CN116144127B_ABST
Patent Text Reader

Abstract

The invention relates to a low dielectric loss PTFE in-situ fiberized FEP microporous material, a preparation method and an application in a wave-transmitting material, and belongs to the technical field of porous foaming materials. Perfluoropropylene (FEP) and polytetrafluoroethylene (PTFE) are mixed to prepare an in-situ fiberized polytetrafluoroethylene reinforced nanocomposite material. The addition of PTFE nanofibers can significantly improve the rheological properties of the material. In the molding and foaming process using supercritical CO2 as a foaming agent, the strain hardening effect and the obvious changes in the viscoelastic response of the melt significantly improve the foaming behavior of the material. The FEP nanofiber has a higher foaming ratio and a more uniform cell structure. The FEP / PTFE microporous material is more hydrophobic than a solid plate, and does not affect its excellent flame retardant properties. The dielectric constant and dielectric loss of the composite material at 10GHz are 1.13 and 0.00015, respectively.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a low dielectric loss PTFE in-situ fiber-forming FEP microporous material, a preparation method and application in wave-transmitting materials, and belongs to the technical field of porous foaming materials. Background Art

[0002] With the advent of the 5G era, large-scale integrated circuits are developing rapidly, and electronic devices are bound to develop in the direction of miniaturization, high speed, high integration and low energy consumption. However, the signal delay effect caused by interlayer capacitance, metal wire resistance and inter-wire capacitance limits the development of ultra-large-scale integrated circuits. It is generally believed that when the signal reaches the GHz level and above, the skin effect of the conductor becomes more obvious, the dielectric leakage effect begins to become prominent, and the loss of the transmission line becomes non-negligible. The main sources of loss are conductor loss and dielectric loss. Other types of loss, such as radiation loss, are usually relatively small. Reducing conductor loss can be started from two aspects. One is to increase the line width of the wiring, and the other is to reduce the roughness of the copper foil. In high-frequency and high-speed PCB boards, devices need to be highly integrated and miniaturized, so the increase in line width is limited; the roughness of the copper foil is also getting smaller and smaller. Therefore, it is necessary to start from reducing dielectric loss, and dielectric loss has nothing to do with the structure of the transmission line. To reduce the loss of the transmission line, the only way is to use materials with a lower loss angle. At present, the PCB substrates used in industrial applications include FR-4 epoxy glass fiber board (epoxy board), glass fiber cloth reinforced polytetrafluoroethylene (PTFE), olefin polymer and polyimide resin (PI), etc. However, if they are used for high-frequency signal transmission, the currently used materials are not suitable because of poor processing performance or too high dielectric loss. Therefore, it is urgent to develop high-performance materials with ultra-low dielectric constant and dielectric loss.

[0003] Fluorinated ethylene propylene (FEP, F46) is a copolymer of tetrafluoroethylene (TFE) and hexafluoropropylene (HFP). Its molecular structure is equivalent to the structure formed by replacing some fluorine atoms on the PTFE molecular chain with trifluoromethyl. The introduction of HEP monomer units is equivalent to destroying the symmetry of the PTFE molecular chain. Its crystallinity, melting point and viscosity make FEP a fluoroplastic with excellent comprehensive performance. It can be plasticized and processed. Except that its maximum operating temperature is 50°C lower than PTFE, its other performances are equivalent to PTFE. Its operating temperature range is -190~205°C, which makes FEP a convenient substitute for PTFE in many aspects, especially in high-performance, low-dielectric applications, including communications, aerospace, and high-frequency electronic equipment. However, when FEP materials are used in wave-transmitting equipment products, there are still problems with poor dielectric properties and high wave transmission loss. Summary of the invention

[0004] The technical problem to be solved by the present invention is that when the FEP material in the prior art is directly used in the material of the wave-transmitting device, there are problems such as low dielectric properties and large wave transmission loss. The present invention proposes a FEP supercritical foaming material after adding PTFE. By using PTFE in FEP, its rheological processing properties are significantly improved, the foaming ratio is increased, and the dielectric constant of the material is reduced.

[0005] The technical solution is:

[0006] The low dielectric loss PTFE in-situ fiberized FEP microporous material is mainly made of FEP and contains PTFE fibers; the content of PTFE in FEP is in the range of 0.1-10wt%; the diameter of PTFE fibers is 100-500nm; the microporous material is prepared by supercritical foaming method, and the pore diameter of the microporous material is 20-200μm, and the pore density is 1×10 6 ~1×10 10 Pieces / cm 3 .

[0007] The microporous material has a dielectric constant of 0.00015-0.00050 under the condition of 2.5 GHz to 10 GHz.

[0008] The microporous material has a water drop contact angle of 120-140° on its surface.

[0009] The method for preparing the low dielectric loss PTFE in-situ fiber-forming FEP microporous material comprises the following steps:

[0010] Step 1, mixing PTFE fiber with FEP masterbatch, and then vulcanizing to obtain FEP / PTFE nanocomposite material;

[0011] Step 2: Process the FEP / PTFE nanocomposite material by supercritical foaming to obtain a microporous material.

[0012] In the step 1, the temperature of the mixing process is 270-320° C.; the temperature of the vulcanization process is 300-350° C., and the pressure is 5-15 MPa.

[0013] In the step 2, the supercritical foaming conditions are temperature 235-265° C., pressure 15-20 MPa, and time 50-200 min.

[0014] Application of the above-mentioned microporous material in wave-transmitting material.

[0015] The wave-transmitting material is a PCB board; in the application, PTFE fiber is used to improve the foaming ratio and dielectric properties of the microporous material.

[0016] The application also includes a method for predicting wave transmission performance, comprising the following steps:

[0017] Calculate the overall wave transmittance T1 of the foamed material considering the pore structure; calculate the equivalent wave transmittance T2 of the material when the material is regarded as a homogeneous medium, calculate the accuracy α of the data set, and use the genetic algorithm to find the minimum value of α, and the corresponding values ​​of the real part of the equivalent dielectric constant and the imaginary part of the equivalent dielectric constant are the calculated values;

[0018]

[0019] In the formula, ε' f is the real part of the equivalent dielectric constant, ε” f is the imaginary part of the equivalent dielectric constant.

[0020] The transmittance T1 is calculated by the following steps:

[0021]

[0022] θ1 is the incident angle, n c is the number of cell walls encountered by electromagnetic waves when penetrating the foaming material, d c is the cell diameter, d w is the average thickness of the cell wall; L is the thickness of the material flat plate;

[0023] T p and T s represent the transmission coefficients of TM mode and TE mode respectively;

[0024] T p / s =|t| 2 ; Subscript represents p or s;

[0025]

[0026] i is the imaginary number symbol, β is the phase thickness, where λ is the wavelength, c is the speed of light, f is the frequency, and θ2 is the refraction angle; t 12 ,t 23 The reflection coefficient and wave transmission coefficient of medium 1→2 and 2→3 are respectively;

[0027] For the TE mode, it is calculated by the following formula:

[0028]

[0029] For the TM mode, it is calculated by the following formula:

[0030]

[0031] x and y represent the medium before the incident interface of the electromagnetic wave and the medium after the interface, respectively. When the values ​​are 1, 2, and 3, they represent the air medium, the foam material flat medium, and the air medium on the path of the electromagnetic wave when it comes, respectively; N is the complex refractive index N j =n j +ik j , the real part of the refractive index and the extinction coefficient are n j , k j , j is the medium represented, j = 1, 2 or 3.

[0032]

[0033] λ is the wavelength, θ2 is the refraction angle, u2 and v2 are intermediate variables set to simplify the calculation, satisfying the following formula:

[0034]

[0035] ρ 12 , 23 , τ 12 , τ 23 They are respectively expressed as the reflection coefficient and transmission coefficient of medium 1 → medium 2 and medium 2 → medium 3, represents the reflection phase and is calculated by the following formula:

[0036]

[0037] p1=n1cosθ1;

[0038] n1, n2 and k2 are determined by calculating the real and imaginary parts of ε' and tanδ:

[0039] When the subscript j takes the values ​​of 1, 2, and 3, it represents the air medium, the foam material flat medium, and the air medium on the path of the electromagnetic wave when it comes, respectively; ε' is the real part of the dielectric constant; tanδ is the dielectric loss tangent.

[0040] Beneficial Effects

[0041] 1. The present invention adopts an in-situ fiber-forming process to prepare the FEP / PTFE blend, and a supercritical CO2 compression foaming method to obtain the microporous foam.

[0042] 2. FEP has an extremely low dielectric constant (2.1) and dielectric loss (0.00085). Compared with polytetrafluoroethylene (PTFE), FEP has better processing performance and does not affect other excellent properties, such as flame retardancy, hydrophobicity and oleophobicity.

[0043] 3. The added PTFE microspheres are stretched into fibers and even entangled into a mesh structure through the strong shear force of the torque rheometer, which changes the viscoelasticity of the FEP matrix, thereby further promoting the foaming of the nanocomposite material, inhibiting the pore breaking behavior in the subsequent foaming process, and increasing the foaming ratio. After the introduction of micropores, the contact angle of the FEP microporous material is greatly increased, and the dielectric constant and dielectric loss are greatly reduced, without affecting its excellent corrosion resistance and flame retardancy. It is suitable for high-frequency and high-speed PCB applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 : Scanning electron microscopy (SEM) of PTFE fiber morphology in FEP matrix: a) 0-PTFE, b) 0.5-PTFE, c) 1-PTFE, d) 3-PTFE, e) 5-PTFE

[0045] Figure 2 : DMA curve and DSC curve of FEP / PTFE composite material

[0046] Figure 3 :Effects of PTFE nanofibers on shear rheological properties at 290 °C: (a) storage modulus (G′), (b) loss modulus (G″), (c) complex viscosity (|η*|) and (d) loss tangent (tanδ)

[0047] Figure 4 :Extensional viscosity of FEP / PTFE nanocomposites at different stretching rates at 290℃: (a: 0-PTFE, b: 0.5-PTFE, c: 1-PTFE, d: 3-PTFE and e: 5-PTFE) and tensile hardening index χ E

[0048] Figure 5 :SEM images of FEP / PTFE nanocomposites at 248°C: (a: 0-PTFE, b: 0.5-PTFE, c: 1-PTFE, d: 3-PTFE and e: 5-PTFE)

[0049] Figure 6 :Foaming ratio, cell density and cell diameter of FEP / PTFE nanocomposites

[0050] Figure 7 :Measurement and calculation of dielectric constants of FEP / PTFE foams with different expansion ratios at different frequencies: (a) 2.5 GHz (b) 5 GHz (c) 10 GHz

[0051] Figure 8 :Measurement and calculation of dielectric loss of FEP / PTFE foam with different expansion ratios at different frequencies: (a) 2.5GHz (b) 5GHz (c) 10GHz

[0052] Fig. 9 :Water wettability of PMI and FEP / PTFE nanocomposite foam materials

[0053] Fig.10 :Wettability of soybean oil in FEP / PTFE nanocomposite foaming materials

[0054] Fig.11 :PMI foam and FEP foam soaked in alkali solution

[0055] Fig.12 :Vertical combustion test of PMI foam and FEP / PTFE foam (a~d are the combustion pictures of PMI foam, e is the picture of the melting and dripping of FEP / PTFE foam specimen, f~i are the combustion pictures of FEP / PTFE foam, and j is the picture of FEP / PTFE foam after combustion)

[0056] Fig.13 This is a schematic diagram of the wave transmission process of foam materials

[0057] Fig.14 This is the flow chart of the inversion method for calculating the equivalent dielectric constant DETAILED DESCRIPTION

[0058] The development of polymer dielectric materials with ultra-low dielectric constant and dielectric loss, high temperature resistance, corrosion resistance, hydrophobicity and flame retardancy is of great significance to meet the requirements of low-latency and high-transmission dielectric materials in the 5G field. In-situ fiberized polytetrafluoroethylene reinforced nanocomposites were prepared by mixing perfluoropropylene (FEP) with polytetrafluoroethylene (PTFE) using a torque rheometer. PTFE nanofibers with a diameter of less than 500nm and a large aspect ratio were prepared. The experimental results of shear rheometer and extensional rheometer showed that the addition of PTFE nanofibers can significantly improve the rheological properties of the material. In the molding and foaming process with supercritical CO2 as the foaming agent, the strain hardening effect and the obvious change of the viscoelastic response of the melt significantly improved the foaming behavior of the material. FEP nanofibers have a higher foaming ratio and a more uniform cell structure. When the polytetrafluoroethylene fiber content is 0.5%, its foaming performance is the best. FEP / PTFE microporous materials are more hydrophobic than solid sheets without affecting their excellent flame retardant properties. In addition, the dielectric constant and dielectric loss of FEP / PTFE composite materials at 10GHz are 1.13 and 0.00015 respectively, which meets the needs of low-latency and high-transmission PCB boards.

[0059] Example 1 Preparation of FEP / PTFE Nanocomposite Materials

[0060] A torque rheometer was used to mix a certain amount of PTFE and FEP at 290°C for 12 minutes at a mixing speed of 60 rpm to obtain a FEP / PETE nanocomposite material, which was then pressed into various sheets at 330°C and 10 MPa using a flat vulcanizer for use. Table 1 shows the composition of the nanocomposite material.

[0061] Table 1 Composition of FEP / PTFE nanocomposites

[0062]

[0063] Example 2 Supercritical Carbon Dioxide Foaming

[0064] The foamed samples were prepared by intermittent foaming process using CO2 as a physical foaming agent. 3 The sample was placed in a high-pressure foaming kettle to dissolve CO2. Before pressurization, the autoclave was heated to a certain temperature and three CO2 purges were used to remove the air in the high-pressure foaming kettle. The high-pressure foaming kettle was then pressurized to the required pressure using an ISCO high-pressure pump (260D, USA). The sample was saturated in the autoclave at a temperature of 245°C, 248°C, 251°C, 254°C, 257°C, and a pressure of 18MPa for 90min. Then, it was foamed by rapid decompression for 2s.

[0065] Characterization methods

[0066] 1. Foaming ratio measurement

[0067] The foam density is determined by the water displacement method (ASTM D792). The expansion ratio (ER) is measured after 3 days of foaming. The ER is calculated as:

[0068]

[0069] where ρ solid and ρ foam are the densities of solid and foam samples, respectively.

[0070] 2. Scanning Electron Microscopy

[0071] Scanning electron microscopy was used to observe the cross-section of FEP / PTFE nanocomposites and the cellular morphology of microcellular foams at an accelerating voltage of 10 kV. The nanocomposites and foams were cryogenically fractured in liquid nitrogen, and then gold was coated on their fractured cross-sections. The average cellular diameter size (D) and average cellular density (N) were further obtained from the SEM micrographs using Image J-Pro software. f ). Take at least 3 micrographs for each sample to calculate the average value as shown below

[0072]

[0073] Where N is the number of cells in the SEM micrograph and A is the micrograph area (cm 2 ).

[0074] 3. Differential Scanning Calorimetry

[0075] The samples (4-10 mg) were subjected to differential scanning calorimetry (DSC, TA Q250) experiments under nitrogen atmosphere, heating from 40°C to 350°C at a heating rate of 10°C / min to eliminate the thermal history, then cooling down to 40°C at a cooling rate of 10°C / min, and finally heating from 40°C to 350°C at a heating rate of 10°C / min. With thermal properties, it enables us to determine the foaming temperature range of FEP / PTFE nanocomposites and the miscibility of FEP and PTFE.

[0076] 4. Thermogravimetric analysis

[0077] In order to measure the degradation temperature of FEP and FEP / PTFE nanocomposites and to study the changes in the molecular chain structure before and after blending, thermogravimetric analysis (TGA) was performed using a TGA550 instrument. The program temperature range was set at 800°C at room temperature and the heating rate was 10°C / min under a nitrogen atmosphere.

[0078] 5. Dynamic mechanical analysis

[0079] Dynamic mechanical analysis tests were performed in tension mode. The samples were trimmed into 20 mm long, 5 mm wide plates with a thickness of 1 mm. The loss tangent (tanδ) of all samples was measured in the temperature range of -140°C to 150°C at a heating rate of 3°C / min and a frequency of 1 Hz.

[0080] 6. Dielectric properties analysis

[0081] A vector network analyzer was used to connect a single-frequency separated dielectric resonant cavity fixture to measure the dielectric constant and dielectric loss of the samples at frequencies of 2.5 GHZ, 5 GHz and 10 GHz.

[0082] 7. Contact angle test

[0083] The contact angle system was used to measure the contact angle of water and soybean oil on FEP and FEP / PTFE nanocomposite films and foams, as well as polymethacrylimide foam (PMI). Water was dropped onto the sample surface to measure the contact angle.

[0084] 8. Analysis of flame retardant properties

[0085] Vertical combustion tests were conducted on PMI, FEP and FEP / PTFE composite foam materials using a horizontal vertical combustion measuring instrument in accordance with the UL94 standard. All specimens were cut at 125×15×3mm. The total time for the specimens to burn was recorded. The limiting oxygen index (LOI) of PMI foam was measured using a limiting oxygen index tester in accordance with the ASTM D2863 standard.

[0086] Morphology Analysis of FEP / PTFE Nanocomposites

[0087] like Figure 1 This is a SEM image of FEP / PTFE nanofiber composite material. As the PTFE content increases, the number and diameter of the fibers increase. The diameter of the fiber is less than 500nm, so the aspect ratio can be very high. Many fibers are entangled together to form a network structure, which can improve the matrix melt strength and effectively prevent the pores from breaking during the foaming process. When the dispersed phase content is low, the probability of the dispersed phase molecules meeting each other is low. Under the action of tensile stress, the diameter of the sub-fibers gradually decreases. As the dispersed phase content increases, during the fiber formation process, the ellipsoids collide, condense and entangle with each other, forming a fiber network structure.

[0088] Thermodynamic Analysis of FEP / PTFE Nanocomposites

[0089] The thermal behavior of FEP / PTFE nanocomposites was investigated using differential scanning calorimetry (DSC), considering both the melting and crystallization processes. Figure 2 The a region is the Tanδ diagram of the nanocomposite tested by DMA. From the Tg temperature, it can be seen that FEP and PTFE are thermodynamically incompatible. Figure 2 Region b is the secondary heating curve of PTFE / FEP blends with different contents, pure FEP and pure PTFE. The lower melting point (Tm1) corresponds to the melting point temperature of pure FEP; the higher melting point (Tm2) corresponds to polytetrafluoroethylene. It can be seen that the melting temperature of FEP in the mixture (255-257℃) is lower than that of pure FEP (259℃). The melting enthalpy of the sample with polytetrafluoroethylene nanofibers is also slightly lower, indicating that its crystallinity is lower due to the hindering effect of nanofibers.

[0090] Table 1 Melting temperature (Tm1, Tm2), glass transition temperature (Tg), and secondary transition (Tβ) of samples

[0091]

[0092] *https: / / www.sigmaaldrich.cn / CN / zh / product / aldrich / 182478

[0093] Rheological properties analysis

[0094] In the process of compression foaming, the rheological properties of the melt play a vital role. In order to study the effect of polytetrafluoroethylene nanofibers on the shear rheological properties of nanocomposites, small amplitude oscillatory shear (SAOS) tests were carried out in the linear viscoelastic region at 290 °C. The relationship between the storage modulus (G′) and the loss modulus (G″) and the shear rate (ω) is shown in Figure 3 As shown in the a and b areas of . With the increase of polytetrafluoroethylene (PTFE) content, the values ​​of G′ and G″ in the low frequency area tend to increase, but in the high frequency area, they decrease with the increase of PTFE content. The decrease of viscosity in the high frequency area is beneficial to the processing of composite materials, and the increase of viscosity in the low frequency area is beneficial to the stability of the foam cells and the inhibition of rupture during the foaming process. When structural changes occur, G′ is more sensitive than G″. Figure 3 As shown in a, the G' values ​​of samples 0.5-PTFE, 1-PTFE, 3-PTFE and 5-PTFE deviate from the G' value of sample 0-PTFE, indicating that there is a strong interaction between the generated PTFE and the FEP matrix. In addition, a platform area can be observed in the low-frequency region of the sample with added PTFE. Considering that polytetrafluoroethylene nanofibers can be interwoven into a mesh or network structure, the strong interaction between the dispersed phase and the continuous phase makes the polymer melt exhibit a solid or gel-like viscoelastic response. The change in the elastic response of PTFE nanofiber reinforced FEP melt is expressed by tanδ, where δ is the loss angle, calculated by dividing G″ by G′. From Figure 3 As can be seen from the graph d, compared with the 0-PTFE sample, the tanδ of all samples with PTFE nanofibers has a significant downward trend, especially in the low-frequency region, which means that these melts have a higher elastic response. The presence of nanofibers and the network structure can greatly enhance the viscoelasticity of the nanocomposite melt and effectively hinder the merging and rupture of the cells during the cell growth stage.

[0095] When the cell is growing, the cell wall undergoes biaxial stretching, so the elongation viscosity of the melt plays an active role in the cell growth. Based on the shear rheological test, the elongation viscosity of the melt at different stretching rates (0.01~1s -1 ) The extensional viscosity η of the sample + (t,ε). Figure 4 The extensional viscosity curves of FEP with different PTFE contents are shown. Figure 4 As shown in a, due to the lack of branched chains and polytetrafluoroethylene nanofibers, sample 0-PTFE has no strain hardening phenomenon. The other samples with added PTFE have a strain hardening phenomenon in the range of 0.01 to 1s -1 At strain rates of , PTFE nanofiber composites exhibit obvious strain hardening phenomenon.

[0096] The variation of the extensional viscosity is described in detail using a quantitative analysis method. The strain hardening factor χ E The definition of is shown in the following formula. + (t) is the transient shear viscosity. In this study, η + (t,ε) is the value when the Hencky strain reaches 1.0.

[0097]

[0098] 0.01~1s -1 At a strain rate of E is less than 1, showing strain softening behavior. This phenomenon is due to the unbranched structure of FEP, where all samples containing PTFE nanofibers have a χ value of 0. E The values ​​are very high. As discussed in the shear rheology test, the fiber network can lead to a longer relaxation process. The existing nanofibers hinder the stretching and flow of the FEP matrix. The significant strain hardening indicates that the introduction of PTFE nanofibers can change the extensional rheological behavior of FEP.

[0099] Forming and Foaming of FEP / PTFE Nanocomposites

[0100] The foaming experiment was carried out on a compression foaming device equipped with an air injection pump. The cavity pressure was 18MPa, the saturation time was 90min, and the temperature was 245℃-257℃. Foaming temperature is one of the important parameters for regulating the foaming ratio and pore structure of polymers. As can be seen from the figure, the properties of FEP are closer to those of amorphous polymers as the foaming temperature increases. As the foaming temperature increases, the crystals in the FEP / PTFE sample will partially or completely melt, and the pore size will gradually increase. As expected, the pore diameter increases with the increase in the foaming ratio, and the pore diameter decreases with the increase in the foaming ratio. However, when the temperature is raised to 257℃, there is no obvious increase in the foaming ratio compared to 254℃, and it even decreases. The corresponding foaming ratio and pore diameter also change accordingly. As the foaming temperature increases, on the one hand, the degree of freedom of FEP molecules increases, and its deformation energy is greatly enhanced, which is more conducive to the growth and aggregation of bubbles; on the other hand, the solubility of CO2 molecules in the polymer matrix decreases, which is obviously not conducive to the growth and expansion of bubbles. Obviously, when the temperature reaches 257°C, the melt viscosity of FEP and its composite samples becomes lower, and even the gas cannot be contained, and the bubbles collapse, etc., which shows a decrease in the foaming ratio in the macroscopic view. Below 254°C, as the temperature increases, although the solubility of CO2 molecules in the polymer matrix decreases, the change in deformation ability brought about by the increase in temperature is better in the competition, and there is no large-scale hole collapse phenomenon like at 257°C, which shows an increase in the foaming ratio in the macroscopic view. Compared with pure FEP samples, the expansion ratio increases after adding PTFE. This may be because the addition of PTFE destroys the relatively regular crystal structure of the FEP molecular chain, causing more CO2 to dissolve under corresponding conditions. The fiber network formed after the addition of PTFE can effectively inhibit pore breakage without being unable to contain the gas. Therefore, it is manifested macroscopically as an increase in the expansion ratio, a decrease in the corresponding pore density, and an increase in the pore diameter.

[0101] Relationship between dielectric behavior and expansion ratio (ER) of FEP / PTFE foam

[0102] So far, several theoretical models, including the modified Clausius–Mossotti expression (1), the Lichteneck formula (2), the Maxwell–Garnett theory (3) and the Jayasundere–Smith model (4) have been developed for predicting the effective dielectric constant of dielectric materials.

[0103]

[0104] As for FEP / PTFE microporous foam, it consists of two parts: pores filled with air and cell walls composed of FEP / PTFE matrix. In order to accurately study the relationship between dielectric constant and foaming, the theoretical dielectric constant at the expansion ratio of 2.5 GHz, 5 GHz and 10 GHz (ε1 = 2.1 for FEP or FEP / PTFE and ε2 = 1.0 for dry air) was investigated ( Figure 7 ). In addition, the dielectric constant values ​​of FEP / PTFE foam measured at 2.5GHz, 5GHz and 10GHz are also shown in the figure. Obviously, the experimental results of FEP / PTFE foam show that the above model can be used to predict the dielectric constant of FEP / PTFE foam. Based on this result, if a 10-fold foaming ratio can be obtained, the dielectric constant of FEP / PTFE foam will theoretically drop further to below 1.1. As for the dielectric loss, it also decreases with the increase of the foaming ratio of FEP / PTFE foam. In addition, as the frequency changes, from 2.5GHz to 10GHz, the dielectric constant and dielectric loss are very stable. More importantly, FEP / PTFE foam has achieved an ultra-low dielectric constant as low as 1.13 (Table 2), which is lower than the lowest value of most reported low-k dielectrics, and a dielectric loss of 0.00015 ( Figure 8 ), which is the lowest value reported so far for low dielectric loss materials. Combined with ultra-low dielectric constant and dielectric loss, PEN foam has great application potential in 5G communication integrated circuits.

[0105] Hydrophobic and oleophobic properties

[0106] Hydrophobicity is a more important parameter for high-performance materials in electronics and microelectronics because it controls the adsorption of water and the deterioration of dielectric properties. The water wettability of FEP / PTFE foam materials is as follows: Fig. 9 As shown in the figure, it can be seen that the water contact angle of the FEP foam sample is about 30° higher, from 110° to 140°. The surface roughness of the foamed material increases, so the hydrophobicity of the FEP / PTFE foam material is further improved. Compared with PMI foam, it shows hydrophilic properties, and the water contact angle is as low as 77.4°. Fig.10 As shown in the figure, FEP / PTFE foam also exhibits oleophobic properties for soybean oil with low surface energy, and its oil contact angle is as high as 115.6°, and its contact angle remains unchanged. However, the oil contact angle of PMI foam is as low as 31.6°. Combined with its excellent hydrophobic and oleophobic properties, FEP / PTFE foam can be better used in extremely humid oil-containing media environments.

[0107] Corrosion resistance

[0108] The circuit manufacturing process of the circuit board generally involves the copper etching process. Based on the copper clad laminate, after the pattern transfer, the copper outside the circuit area is etched away by pattern electroplating or dry film cover hole, and finally the dry film or anti-corrosion metal is removed to form the circuit. Alkaline etching is a commonly used etching method. Therefore, the copper clad laminate is required to have a certain degree of alkali corrosion resistance. After the PMI foam is immersed in 10% NaOH solution at 70°C for 10 hours, the PMI foam shows obvious swelling phenomenon on a macro scale. Because the PMI molecule will hydrolyze with the alkali solution, the reaction equation is as follows.

[0109]

[0110] The appearance of FEP foam remains almost unchanged. Fig.11 The SEM images before and after alkali solution immersion show that the cell walls of PMI foam have been corroded and turned into large and broken pores, while the cell structure of FEP foam has hardly changed. Corrosion is one of the most serious problems in the industrial world, and the excellent corrosion resistance of FEP foam gives it a greater competitive advantage in the PCB field.

[0111] Flame retardant properties

[0112] Vertical combustion test of PMI foam and FEP / PTFE foam Fig.12 As shown in the experimental video, see SIVIDEO1. It can be seen that PMI foam can be easily ignited ( Fig.12 a, b), and the dripping melt ignited the cotton layer below ( Fig.12 c, d). When FEP / PTFE foam is ignited for the first time, it burns under the flame of the Bunsen burner ( Fig.12 f), self-extinguishing when away from fire ( Fig.12 g), and 10s after the second ignition, the fire also extinguished itself ( Fig.12 h, f), some of the molten material dripped and failed to ignite the cotton layer ( Fig.12 e), the FEP / PTFE foam after secondary combustion is still almost pure white above ( Fig.12 J), proving the excellent low smoke flame retardant properties of FEP / PTFE foam.

[0113] Performance prediction and calculation of PTFE in-situ fiber-forming FEP microporous materials

[0114] The present invention also predicts and calculates the electromagnetic wave transmission performance of the composite foam material, and the specific process is as follows:

[0115] like Fig.13As shown in the figure, assuming that the foam material as a whole is a flat plate with a thickness of L, the air on the path of the incoming electromagnetic wave is defined as medium 1, the foam material flat plate is medium 2, and the air on the path of the outgoing electromagnetic wave is medium 3, whose real part of refractive index and extinction coefficient are n respectively. j , k j , j is the medium represented (j = 1, 2, 3), then the complex refractive index is N j =n j +ik j By inputting the real part of the dielectric constant (ε'), the imaginary part of the dielectric constant (ε") or the dielectric loss tangent (tanδ) of the composite matrix (which can be obtained through experiments), as well as the foaming ratio (ER) and pore size (d c ) to obtain the transmittance (T) and reflectivity (R) of the foamed material.

[0116] For a uniform dielectric plate, this model only considers the vector addition of the first reflection (transmission) and the second reflection (transmission), and the calculation formulas for the reflection coefficient and transmission coefficient are as follows:

[0117]

[0118] r 12 、r 23 ,t 12 ,t 23 The reflection coefficient and transmission coefficient of medium 1→2 and 2→3 are respectively, where r 12 、r 23 ,t 12 ,t 23 It can be solved by Fresnel formula; β is the phase thickness, and its value is:

[0119]

[0120] d w is the average thickness of the cell wall; λ is the wavelength of the electromagnetic wave, and its value in the medium is inversely proportional to the refractive index (complex numbers can be used here for calculation), c is the speed of light, f is the frequency, and n n is the refractive index of the medium in this layer, and n1, n2 and n3 are defined as the refractive indices of the upper wall, the pore wall and the lower wall of the pore wall, respectively.

[0121] The total reflectivity R and transmittance T are shown in formula (3):

[0122]

[0123] θ1 is the angle of incidence, θ2 is the angle of refraction;

[0124] The p value corresponds to the q value, which is an intermediate variable corresponding to the characteristic impedance of the dielectric layer. The p value corresponds to the vertical polarization and the q value corresponds to the horizontal polarization, as shown in formula (4). When calculating the vertical polarization, the p value is substituted into formula (3). When calculating the horizontal polarization, the q value is substituted into formula (3). In the foaming material, the air around the pore wall is p1=p3, q1=q3.

[0125]

[0126] In formula (5), represents horizontal polarization, which can be used to calculate TM mode, and in formula (6), represents vertical polarization, which can be used to calculate TE mode. x and y represent the medium before the incident interface of the electromagnetic wave and the medium after the interface, respectively:

[0127]

[0128]

[0129] When x=1、y=2, we can calculate t 12 and r 12 , and so on…

[0130] The calculations of TM mode (p-wave) and TE mode (s-wave) are independent of each other and do not affect each other. N1 and N2 are complex refractive indices.

[0131]

[0132] A=1-TR

[0133] The TE mode transmittance (T TE ) and reflectivity (R TE ), and the TM mode transmittance (T TM ) and reflectivity (R TM ).

[0134] After adding the cellular structure, the overall reflectivity is R+RT 2 +…+RT 2m The transmittance and reflectance of the overall material are calculated by formula (5):

[0135]

[0136] Where n c is the number of cell walls encountered by electromagnetic waves when penetrating the foaming material, calculate n c It is assumed that the pores are evenly arranged along the electromagnetic wave transmission path.

[0137] Dielectric constant and dielectric loss are the most representative indicators of the dielectric properties of materials. Here, a method for solving the equivalent dielectric constant of foaming materials is proposed based on the inversion method. The specific flow chart is as follows Fig.14 As shown, the basic steps can be summarized as:

[0138] (1) The dielectric constant and dielectric loss of the material before foaming, as well as the pore size and foaming ratio of the foamed material after foaming are input and combined with the electromagnetic wave frequency to obtain the calculated value T1 of the transmittance of the foamed material, which is calculated by formula (6).

[0139] (2) Then input the dielectric constant ε' of the unfoamed material with the same thickness as the foamed material f and the imaginary part of the dielectric constant ε" f The solution interval (for example, ε' f is 1 to 2, ε” f is 0~0.01), and its wave transmittance T2 is directly calculated as the solution interval;

[0140]

[0141] λ is the wavelength, θ2 is the refraction angle, u2 and v2 are intermediate variables set to simplify the calculation, satisfying the following formula:

[0142]

[0143] ρ 12 , 23 , τ 12 , τ 23 They are respectively expressed as the reflection coefficient and transmission coefficient of medium 1 → medium 2 and medium 2 → medium 3, represents the reflection phase and is calculated by the following formula:

[0144]

[0145] p1=n1cosθ1;

[0146] n1, n2 and k2 are determined by calculating the real and imaginary parts of ε' and tanδ:

[0147] When the subscript j takes the values ​​of 1, 2, and 3, it represents the air medium, the foam material flat medium, and the air medium on the path of the electromagnetic wave when it comes, respectively; ε' is the real part of the dielectric constant; tanδ is the dielectric loss tangent.

[0148] α is the simulation accuracy, which indicates how close T1 is to T2.

[0149]

[0150] In the calculation, let α be the smallest. At this time, ε' of the uniform dielectric plate is f and ε” f, which are the simulated values ​​of the real and imaginary parts of the dielectric constant of the foam material.

[0151] (3) In the calculation, the genetic algorithm used continuously approaches α to the minimum value through crossover, mutation, and iteration. After about 50 iterations, the value of α is 10 -8 The speed and accuracy of calculation are improved by optimizing the algorithm. Table 2 shows the measured and simulated values ​​of foaming materials.

[0152] Table 2. Measured dielectric properties and simulated values ​​of PTFE in-situ fiberized FEP microporous materials

[0153]

[0154]

Claims

1. The application of low dielectric loss PTFE in-situ fiberized FEP microporous material in wave-transmitting materials is characterized by: The main material of the low dielectric loss PTFE in-situ fiber-forming FEP microporous material is FEP, and it also contains PTFE fibers; the content of PTFE in FEP is in the range of 0.1-10wt%; the diameter of PTFE fiber is 100-500nm; the microporous material is prepared by supercritical foaming method, and the pore diameter of the microporous material is 20-200μm, and the pore density is 1×10 6 ~1×10 10 Pieces / cm 3 ; The application also includes a method for predicting wave transmission performance, comprising the following steps: Calculate the overall wave transmittance T1 of the foamed material considering the pore structure; calculate the equivalent wave transmittance T2 of the material when the material is regarded as a homogeneous medium, calculate the accuracy α of the data set, and use the genetic algorithm to find the minimum value of α, and the corresponding values ​​of the real part of the equivalent dielectric constant and the imaginary part of the equivalent dielectric constant are the calculated values; In the formula, ε' f is the real part of the equivalent dielectric constant, ε” f is the imaginary part of the equivalent dielectric constant; The transmittance T1 is calculated by the following steps: θ1 is the incident angle, n c is the number of cell walls encountered by electromagnetic waves when penetrating the foaming material, d c is the cell diameter, d w is the average thickness of the cell wall; L is the thickness of the material flat plate; T p and T s represent the transmission coefficients of TM mode and TE mode respectively; T p / s =|t| 2 ; Subscript represents p or s; i is the imaginary number sign, β is the phase thickness, where λ is the wavelength, c is the speed of light, f is the frequency, and θ2 is the refraction angle; t 12 ,t 23 The reflection coefficient and wave transmission coefficient of medium 1→2 and 2→3 are respectively; For the TE mode, it is calculated by the following formula: For the TM mode, it is calculated by the following formula: x and y represent the medium before the incident interface of the electromagnetic wave and the medium after the interface, respectively. When the values ​​are 1, 2, and 3, they represent the air medium, the foam material flat medium, and the air medium on the path of the electromagnetic wave when it comes, respectively; N is the complex refractive index N j =n j +ik j , the real part of the refractive index and the extinction coefficient are n j , k j , j is the medium represented, j = 1, 2 or 3; λ is the wavelength, θ2 is the refraction angle, u2 and v2 are intermediate variables set to simplify the calculation, satisfying the following formula: ρ 12 , 23 , τ 12 , τ 23 They are respectively expressed as the reflection coefficient and transmission coefficient of medium 1 → medium 2 and medium 2 → medium 3, represents the reflection phase and is calculated by the following formula: p1=n1cosθ1; the p value corresponds to the q value and is an intermediate variable corresponding to the characteristic impedance of the dielectric layer, p corresponds to vertical polarization and q corresponds to horizontal polarization; n1, n2 and k2 are determined by calculating the real and imaginary parts of ε' and tanδ: When the subscript j takes the values ​​of 1, 2, and 3, it represents the air medium, the foam material flat medium, and the air medium on the path of the electromagnetic wave when it comes, respectively; ε' is the real part of the dielectric constant; tanδ is the dielectric loss tangent.

2. The use according to claim 1, characterized in that: Microporous materials have a water drop contact angle of 120-140° on the surface.

3. The use according to claim 1, characterized in that: The preparation method of low dielectric loss PTFE in-situ fiber-forming FEP microporous material comprises the following steps: Step 1, mixing PTFE fiber with FEP masterbatch, and then vulcanizing to obtain FEP / PTFE nanocomposite material; Step 2: Process the FEP / PTFE nanocomposite material by supercritical foaming to obtain a microporous material.

4. The use according to claim 3, characterized in that: In the step 1, the temperature of the mixing process is 270-320°C; The temperature during the vulcanization process is 300-350°C and the pressure is 5-15MPa.

5. The use according to claim 4, characterized in that: In the step 2, the supercritical foaming conditions are temperature 235-265° C., pressure 15-20 MPa, and time 50-200 min.

Citation Information

Patent Citations

  • Method for preparing perfluoroethylene-propylene microcellular foam material

    CN101580600A

  • Method for measuring optical constants of glass

    CN104749113A

  • Fluoropolymer-carbon dioxide compositions and methods of processing fluoropolymers

    US20030230834A1